Navigating cultural transition: Experiences of international students at a midwestern university - Rajaratnam, Dushani; Giraldo-García, Regina J (Journal of International Students, 2026)
International students make a remarkable contribution to U.S. higher education, but face considerable obstacles during cultural transition. This qualitative study investigated the cultural adaptation experiences of 15 international students at a midwestern university, led by Berry’s acculturation theory. Data from semistructured interviews were analyzed using thematic analysis. The findings revealed that students navigated significant academic and linguistic challenges and adapted a twofold social network, primarily relying on conational peers before seeking cross-cultural connections. While centralized services were valuable, personalized faculty mentorship and peer relationships were the most effective supports, facilitating a shift toward a bicultural identity. The study concludes that successful integration requires a "whole-of-university" approach, implying a need for enhanced peer mentoring and faculty development to foster more inclusive and supportive campus environments.